Educational Engagement Through AR and VR: A Review with Application to Shariah-Compliant Sustainable Garden Concepts - Madihah Mat Idris; Nurul Najwa Nasir; Ahmad syafii’ei Abdul Kudos; Wan Norisma Wan Ismail; Azrul Izwan Ismail (Penerbit USIM, 2025)
International Conference of Quran as Foundation of Civilization (SWAT 2025) : Maqasid al-Quran and the Madani Vision: A Guiding Light for Regional Serenity and Global Unity Organized by : Faculty of Quranic and Sunnah Studies, in collaboration with Nasyrul Quran and Daffodil International University, Bangladesh. Date:12-13 November 2025